THE EFFECT OF TRANSFORMATIONAL LEADERSHIP OF SCHOOL PRINCIPLES AND SCHOOL CLIMATE ON TEACHER JOB SATISFACTION - Nessia SEPTIANA (Journal of Education and Leadership in Education, 2021)
This investigation expects to (1) to know the impact of the head groundbreaking authority to work fulfillment at professional school in Rawamangun, East Jakarta. (2) To know the impact of school environment to work fulfillment at professional school in Rawamangun, East Jakarta. (3) To know the impact of the head groundbreaking initiative to class environment in Rawamangun, East Jakarta. This examination was led at professional school in Rawamangun, East Jakarta. The number of inhabitants in this exploration was professional teachers in Rawamangun, East Jakarta which produced to200 individuals. Through Slovin equation got by133 tests. Inspecting method utilizing straightforward arbitrary testing. Information assortment strategy utilized is expost facto review technique by dispersing survey to the educator who has been tried legitimacy of its dependability as per research directed. Information investigation udes by utilizing distinct examination, T-test and F-test. The exploration results show that (1) the head groundbreaking initiative has a positive and critical impact to work fulfillment at professional school in Rawamangun, East Jakarta. (2) School environment has a positive and huge impact to work satifaction at professional school in Rawamangun, East Jakarta. (3) The head groundbreaking authority has a positive and critical impact to class environment.